Pengaruh Displin Kerja dan Kompensasi terhadap Kinerja Karyawan pada PT Prima Tata Solusindo - Setiavianti, Annisa Putri Ayu; Dwi Kristanto (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the influence of work discipline and compensation on employee performance at PT Prima Tata Solusindo. The background of the research is based on fluctuations in the level of discipline and the emergence of complaints regarding the suitability of compensation, which are suspected to have an impact on employee work effectiveness. This study employs a quantitative method with an explanatory approach using a cross-sectional design. A total of 113 respondents were selected using purposive sampling with a saturated sampling technique. Primary data were obtained through the distribution of Likert-scale questionnaires and analyzed using instrument testing, classical assumption tests, and multiple linear regression analysis to identify the partial and simultaneous effects of the independent variables on the dependent variable. The results of this study are expected to provide empirical evidence regarding the role of work discipline and compensation in improving employee performance, as well as serving as a reference for management in formulating more effective human resource management policies.